2018
DOI: 10.18517/ijaseit.8.5.6434
|View full text |Cite
|
Sign up to set email alerts
|

Credibility Dimensions for Islamic Information in Social Media

Abstract: A new way of spreading knowledge and collaborating with each other to achieve specific objectives has been introduced with the rise of social media, which is a useful communication tool. A growing number of people are using social media in search of information relating to religious learning and practices. The younger generation is one of the primary users of social media; therefore, many Islamic scholars are reaching out to Muslim youths using this channel. However, as people assimilate themselves to the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The results of the assessed studies conducted in diverse geographical locations revealed that there was a strong positive influence of the predictor (IC) variable over the outcome (IAB) variable, confirming that more credible information on social media leads to the frequent adoption of information. Additionally, if the social media users are motivated to assess IC cognitively, the effect on IAB results is even stronger (Kadir et al, 2018;Sundar, 2008). Now social media has penetrated not only our personal but also our professional life as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the assessed studies conducted in diverse geographical locations revealed that there was a strong positive influence of the predictor (IC) variable over the outcome (IAB) variable, confirming that more credible information on social media leads to the frequent adoption of information. Additionally, if the social media users are motivated to assess IC cognitively, the effect on IAB results is even stronger (Kadir et al, 2018;Sundar, 2008). Now social media has penetrated not only our personal but also our professional life as well.…”
Section: Discussionmentioning
confidence: 99%
“…The believability of face-toface conversation usually depends upon situational indicators, such as known attributes of the communicator, including his occupation, fame, expertise, body language, etc., but in online situations, some physical identity-based cues are missing to assess conventionally (Fan and Lederman, 2017). Over the years, researchers have suggested various approaches in previous literature which support assessing the credibility of online information, such as models (Fogg et al, 2001;Fritch and Cromwell, 2001;Kadir et al, 2018;Pee, 2012;Petty and Cacioppo, l986;Metzger, 2007;Wathen and Burkell, 2002;Sundar, 2008), theories (Fogg, 2003;Pinem et al, 2019), cognitive heuristics (Metzger and Flanagin, 2013;Xiao et al, 2018), frameworks and checklists (Flanagin and Metzger, 2000;Hilligoss and Rieh, 2008;Knight and Burn, 2005).…”
Section: Information Credibility From Clay To E-tabletsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one of the significant tasks for web applications is to collect users' opinions from different sources to make this content available after the extraction process both for users and for social network applications, which can benefit from it for personalization and adaptation to user needs [28], [29]. Moreover, in this age of digital information overload, this content must be reliable for users and, hence, information sources must guarantee credibility [30]- [32] through the analysis of their context [33], semantic environment [34] and parameterized constrains [35]. A growing number of people are using social media for searching for information related to other sources.…”
Section: Introductionmentioning
confidence: 99%